2020
DOI: 10.1002/lol2.10148
|View full text |Cite
|
Sign up to set email alerts
|

Low snowpack reduces thermal response diversity among streams across a landscape

Abstract: Snow is an important source of water to rivers, and serves to buffer water temperatures against warming. Climate change is altering air temperature and precipitation patterns, thereby altering how snow accumulates across the landscape and contributes to summer stream flows. Our analyses of summer stream temperatures across a complex river basin show that loss of snowpack has disproportionate effects on streams that are cold under typical climate conditions, thereby homogenizing stream temperatures across the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In addition, median discharge at the regional index gage on the Little Susitna River was positively correlated with winter snow accumulation, which can have significant effects on the sensitivity of stream temperatures to air temperature. Cline, Schindler, Walsworth, French, and Lisi (2020) found that, during low snow years, streams draining high‐elevation watersheds were more responsive to variation in air temperature and that summer water temperatures were 4°C warmer than during high snow years. Given the positive relationship between snowpack and median discharge, years with high median discharge may have had colder stream temperatures than predicted by our hindcasting models, leading to a reduction in juvenile salmon growth and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, median discharge at the regional index gage on the Little Susitna River was positively correlated with winter snow accumulation, which can have significant effects on the sensitivity of stream temperatures to air temperature. Cline, Schindler, Walsworth, French, and Lisi (2020) found that, during low snow years, streams draining high‐elevation watersheds were more responsive to variation in air temperature and that summer water temperatures were 4°C warmer than during high snow years. Given the positive relationship between snowpack and median discharge, years with high median discharge may have had colder stream temperatures than predicted by our hindcasting models, leading to a reduction in juvenile salmon growth and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the positive relationship between snowpack and median discharge, years with high median discharge may have had colder stream temperatures than predicted by our hindcasting models, leading to a reduction in juvenile salmon growth and productivity. The relative influence of snowmelt on summer stream temperatures will vary across watersheds depending upon catchment geomorphology and summer climate (air temperature and cumulative precipitation; Cline et al, 2020). These results suggest populations may respond differently to changing snowpack conditions, mediated in part by varying stream temperatures and their associated effects on productivity.…”
Section: Discussionmentioning
confidence: 99%
“…These changes will predominantly alter the sensitivity of high elevation rivers through changes in water snowmelt contribution. Cline, Schindler, Walsworth, French, and Lisi (2020) observed a larger increase in TS value of steep watersheds streams during low snow years than TS changes of streams draining flat watersheds. This suggests that highland streams become more responsive to variation in regional air temperature as snowpack contribution decreases.…”
mentioning
confidence: 71%
“…This suggests that highland streams become more responsive to variation in regional air temperature as snowpack contribution decreases. Therefore, these watersheds should also be investigated considering that thermal refuges at their confluence with warmer river channels may be at risk (Cline et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation